Women's health: an imAging-based cardiovascular risK-rEdUction Program (WAKE UP) study. Rationale and design - Wasniewski, Samantha; Kfouri Da Silva, Rafaella; Capdeville, Sofía; Rivera Molina, Isabel; Virosta, Elena; Ortiz Cortés, Carolina; Díez-Villanueva, Pablo; Adeba, Antonio; Ruiz Lera, Marta; Muñoz, Lucía; Alonso, David; García, Eva; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular (CV) disease is the leading cause of death in women. Although 80% of CV disease events can be prevented, mortality is projected to increase, particularly in young women.ObjectivesTo promote CV health in women and encourage appropriate lifestyle changes by increasing awareness through vascular ultrasound imaging.MethodsWAKE UP is a prospective case-control study in a target population of 720 asymptomatic women, aged 40–70 years with ≥1 major CV risk factor (RF). Participants will attend a baseline visit and follow-up visits at 6 and 12-months. Each visit will include the assessment of traditional and non-traditional risk factors (age, blood pressure, weight, smoking, diet, physical activity, psychosocial aspects, reproductive factors, family lifestyle), CV risk scores [Fuster-BEWAT Score (FBS) and SCORE], perception of CV disease risk, blood sampling of hormones, lipids, glycemic metabolism, inflammation parameters and omics. At baseline visit, women will be randomized to undergo 2D/3D/strain vascular ultrasound (360 with imaging vs. 360 age- and RF-matched controls without imaging). Main outcomes will include changes from baseline to follow-up in overall knowledge, attitudes, and FBS.ConclusionsWAKE UP trial aims to raise awareness about womeńs CV disease and promote lifestyle changes. Imaging can play a key role by revealing the presence of atherosclerotic plaques in a directly relatable way and thus, larger effects are anticipated in women with plaques. WAKE UP can significantly impact CV prevention by involving innovative actions addressing a major public health need and by fostering complementary and synergistic actions.